Strategy Selection of Property Business in Transit Oriented Development Area (Case Study PT. XYZ) - Sulaksmono, Haris; Ahyudanari, Ervina; Ma’ruf, Buana (Institut Teknologi Sepuluh Nopember, 2019)
The property business in 2018 did experience a downward trend because of the high backlog caused by oversupply. But the prospect of the property business in 2019 is quite promising and is believed to continue to prosper. The research base is a case study at PT XYZ, one of the subsidiaries of BUMN Construction Services which is engaged in the development of the property of the Transit Oriented Development (TOD) area of the Light Rail Transit (LRT) in Jakarta. This study aims to obtain a superior strategy in the competition of the property business in the TOD region which makes added value for PT XYZ so that it can compete with other developers. The company's strategy for PT XYZ was formulated using David's strategy formulation framework, which consisted of input stages, matching stages and decision stages. The Analytical Hierarchy Process (AHP) is used to determine the weight of internal and external strategic factors and Quantitative Strategic Planning Matrix (QSPM) to determine alternative chosen strategies. Based on the results of the QSPM assessment of PT XYZ, founded the construction and pre cast concrete division strategy gets a Total Attractive Score (TAS) of 5.60, higher than PT XYZ cooperates with top property marketing companies for 3 years strategy that gets a score of 4.12